Legal Rehabilitation Efforts to Minimize Drug Abuse Rates as an Evaluation Measure by the Government at the National Narcotics Agency (BNN) of Gorontalo Province - Nur Ismi Pulogu; Roni Lukum; Nopiana Mozin (SEAN Institute, 2026)
Drug abuse in Indonesia, particularly in Gorontalo Province, has reached a critical point that threatens the younger generation and requires a comprehensive evaluation of existing recovery policies. This study aims to analyze the implementation of legal rehabilitation efforts in minimizing the rate of drug abuse and to evaluate the policies of the National Narcotics Agency (BNN) of Gorontalo Province as both preventive and curative measures. The method used is a descriptive qualitative approach with the CIPP (Context, Input, Process, Product) evaluation model, in which data were collected through in-depth interviews, observations, and documentation studies, and then analyzed inductively. The results show that rehabilitation efforts have successfully recovered 727 drug users during the 2021–2024 period. However, their effectiveness is still constrained by the limited number of addiction counselors, inadequate inpatient facilities, and the high level of social stigma within the community. These findings conclude that although rehabilitation policies at BNNP Gorontalo are aligned with the principles of restorative justice, strengthening is still needed in terms of human resources and public education to eliminate social resistance. The implications of this study emphasize the importance of a more integrative policy transformation between law enforcement and sociological support. This research serves as a basis for recommendations to local governments in optimizing narcotics eradication strategies through the enhancement of more humane and accessible rehabilitation facilities.